Vibroarthrography as a Noninvasive Screening Method for Early Diagnosis of Knee Osteoarthritis: A Review of Current Research - Robert Karpiński; Aleksandra Prus; Kamil Jonak; Przemysław Krakowski (Applied Sciences)
The ageing population and the resulting number of physical and health problems are now a major social and economic challenge around the world. Osteoarthritis is a common disease among older people. It can affect any joint, but it most often affects the knee, hip, and hand joints. Osteoarthritis of the knee joint significantly affects everyday life, limiting daily activities. Patients affected by this disease face many ailments, such as pain, stiffness, and a reduced of range of joint motion. In order to implement quick and effective treatment and prevent the development of the disease, accurate and early diagnosis is important. This will contribute to prolonging the health of the joints. Available methods for diagnosing osteoarthritis include conventional radiography, MRI, and ultrasound, but these methods are not suitable for screening. Over the years, there have been proposals to use vibroarthrography as a new, cheap, and noninvasive screening method for cartilage damage. The paper reviews recent studies on vibroarthrography as a diagnostic method for knee osteoarthritis. The aim of the study is to organise the current knowledge regarding the diagnosis of osteoarthritis of the knee joint and vibroarthrography as a proposal for a new diagnostic method.